Prevalence of diabetes and prediabetes and its risk factors in adults aged 25-64 in the Czech Republic: A cross-sectional study - Brož, Jan; Malinovská, Jana; Nunes, Marisa A; Kučera, Kristýna; Rožeková, Katarína; Žejglicová, Kristýna; Urbanová, Jana; Jenšovský, Michael; Brabec, Marek; Lustigová, Michala (Diabetes research and clinical practice, 2020)
AIMS: The aim of this study is to establish the prevalence of diabetes (DM) and prediabetes in the Czech population aged 25-64 years and to evaluate the relationships with various cardiometabolic, sociodemographic, and lifestyle risk factors. METHODS: This was an epidemiological study with a stratified, crosssectional, random sampling design. Sociodemographic, lifestyle, and anamnestic data were collected through interviewer-administered questionnaires, medical examination, and biochemical assays. RESULTS: Among the 1189 participants, 114 were diagnosed with DM (9.6%), 330 with prediabetes (27.8%) and 745 were non-diabetes/non-prediabetes individuals (62.7%). Logistic regression analysis showed that overweight, general and abdominal obesity, hypertension, and lower level of HDL (increased risk) significantly increased the risk of both prediabetes and DM, while living in the cities diminished risk of DM. Among lifestyle variables the significant increased risk of prediabetes and DM was found for smokers and ex-smokers. In other lifestyle variables (marijuana lifetime prevalence, physical activity and frequency of alcohol drinking) the significantly higher or lower risk for prediabetes or DM was not found. CONCLUSIONS: The study shows a high prevalence of DM and prediabetes in the Czech population of age between 25 and 64, providing data on their association with several risk factors.
Keywords: Cardiometabolic Risk Factors; Surveys and Questionnaires; logistické modely; Humans; lidé středního věku; Overweight; Czech population; Hypertension; prevalence; Female; rizikové faktory; dospělí; lidé; kardiometabolické riziko; abdominální obezita; průzkumy a dotazníky; Diabetes Mellitus; Diabetes; Adult; Obesity, Abdominal; Prediabetes; ženské pohlaví; Life Style; Male; životní styl; Middle Aged; hypertenze; Risk factors; prediabetes; Prediabetic State; Czech Republic; Cross-Sectional Studies; EHES; Prevalence; Exercise; Česká republika; mužské pohlaví; diabetes mellitus; cvičení; průřezové studie; Logistic Models; nadváha; Risk Factors